Agro-economic viability from two croppings of broadleaf vegetables intercropped with beet fertilized with roostertree in different population densities - Filho, Francisco Cicupira de Andrade; de Oliveira, Eliane Queiroga; de Lima, Jailma Suerda Silva; Moreira, Joserlan Nonato; Silva, Ítalo Nunes; Lins, Hamurábi Anizio; Filho, Arthur Bernardes Cecílio [UNESP]; Júnior, Aurélio Paes Barros; Neto, Francisco Bezerra (My University, 2020)
The objective of this study was to evaluate the sustainability and agro-economic viability from two croppings of coriander (C) and two of arugula (A) intercropped with beet (B) as a function of roostertree additions to the soil in different population densities. The experimental design was a randomized complete block, with treatments arranged in a 4 x 4 factorial scheme with four replications. The treatments resulted from the combination of four amounts of roostertree biomass (6, 19, 32 and 45 t ha-1 on dry basis) with four population densities of coriander, beet and arugula (20C-50B-20A%, 30C-50B-30A%, 40C-50B-40A% and 50C-50B-50A% of the recommended densities in their single crops). The maximum agronomic efficiency of the polyculture of coriander, beet and arugula was obtained with the density of 40C-50B-40A and the amount of 19 t ha-1 roostertree biomass incorporated into the soil. The highest profitability of the polyculture was obtained with the density of 20C-50B-20A (%) and the amount of 45 t ha-1 of this green manure. High agro-economic efficiency can be obtained by cultivating the polyculture of coriander, beet and arugula when well-manageding the factors of production, fertilization with roostertree and population densities.
Viabilidad agroeconómica de dos cultivos de hortalizas de hoja ancha intercalados con remolacha y fertilizados con roostertree en diferentes densidades de población
Keywords: Agronomic and economic viability; Arugula; Beta vulgaris; Calotropis procera; Coriandrum sativum; Eruca sativa; Polyculture